Nursing research : generating and assessing evidence for nursing practice - Polit, Denise F.; Beck, Cheryl Tatano (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"Thoroughly updated and revised to emphasize the link between research and evidence-based practice, this Ninth Edition of a classic textbook presents state-of-the-art methods for conducting high-quality studies. The ancillary Resource Manual includes application exercises, models of comprehensive research critiques, a full NINR grant application, and a Toolkit on a CD-ROM, containing exemplary research tools (e.g., consent forms, a demographic questionnaire, statistical table templates)--all in easily-adapted Word documents"--Resumé vydavatele
Keywords: ošetřovatelský výzkum -- metodologie; ošetřovatelství založené na důkazech; nursing research -- methodology; evidence-based nursing; monografie; monographs